2015
DOI: 10.3892/ijmm.2015.2290
|View full text |Cite
|
Sign up to set email alerts
|

Bcl10 crucially nucleates the pro-apoptotic complexes comprising PDK1, PKCζ and caspase-3 at the nuclear envelope of etoposide-treated human cervical carcinoma C4-I cells

Abstract: Abstract. Protein kinase (PK)Cζ signaling at various subcellular levels affects cell survival, differentiation, growth and/or apoptosis. However, the mechanisms modulating PKCζ activity at the nuclear membrane (NM) are not yet fully understood. Previously, we demonstrated that PKCζ interacts with the B-cell lymphoma 10 (Bcl10) protein at the NM of human cervical carcinoma (HCC) C4-I cells. In the present study, we aimed to further clarify the interactions between PKCζ, Bcl10 and other proteins co-immunoprecip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Finally, to achieve total cell lysis samples were subjected to one freeze/thaw cycle at −20°C and ice-homogenized with an UltraTurrax™. The protein contents of the extracts were assayed according to Chiarini et al (39, 40) using bovine serum albumin (BSA) as standard.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, to achieve total cell lysis samples were subjected to one freeze/thaw cycle at −20°C and ice-homogenized with an UltraTurrax™. The protein contents of the extracts were assayed according to Chiarini et al (39, 40) using bovine serum albumin (BSA) as standard.…”
Section: Methodsmentioning
confidence: 99%
“…WB was performed as detailed in Chiarini et al (39, 40). Equal amounts of protein lysates (15 μg for the analysis of TKTL1 and CIP-2a and 20 μg for B-MYB) were heat–denatured for 10-min at 70°C in an appropriate volume of 1X NuPAGE LDS Sample Buffer supplemented with 1X NuPAGE Reducing Agent (Life Technologies, Italia).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we report that PDK1 is required for the survival of cortical interneurons but has no obvious effects on cell proliferation and tangential migration. Deletion of Pdk1 in the PDK1 serves as an antiapoptotic factor in a variety of cell types, such as cancer cells, endothelial cells, and skeletal muscle cells [28,61,62,[77][78][79][80][81]. Recently, it was reported that the ablation of Pdk1 in the dorsal telencephalon leads to the increased apoptosis of cortical excitatory neurons at postnatal rather than embryonic stages [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Of the various subtypes of caspases, caspases-3 is the principal caspase actively causing neuronal cell death ( 23 ). Numerous studies have demonstrated that caspase-3 activity increases after cerebral ischemia/reperfusion injury ( 24 , 25 ). In the present study, caspase-3 was induced by GCI.…”
Section: Discussionmentioning
confidence: 99%